1960
DOI: 10.1017/s0022029900010256
|View full text |Cite
|
Sign up to set email alerts
|

The use of ultrafiltration and dialysis in isolating the aqueous phase of milk and in determining the partition of milk constituents between the aqueous and disperse phases

Abstract: A description is given of various methods for the ultrafiltration and dialysis of milk and of the composition of the sera obtained. Ultrafiltrate prepared by the procedure recommended is reasonably representative of the aqueous phase of milk, but its content of lactose and citric acid, and consequently also of calcium, is determined to a slight degree by the sieving phenomenon known to occur often in ultrafiltration. The composition of diffusate obtained from milk at 20 °C is not thought to be controlled to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
1
2

Year Published

1965
1965
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(77 citation statements)
references
References 8 publications
8
66
1
2
Order By: Relevance
“…1). This phenomenon is identical to that observed in cows' milk and it was illustrated by similar sigmoid curves [14,19,26,39]. However, the characteristic points of these curves were different.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…1). This phenomenon is identical to that observed in cows' milk and it was illustrated by similar sigmoid curves [14,19,26,39]. However, the characteristic points of these curves were different.…”
Section: Discussionsupporting
confidence: 85%
“…1) continued until close to the pH observed for cows' milk (pH ~ 4.6) [9,14]. However, contrary to what had been reported for cows' milk [9], the compared changes in solubilization of these two cations (Fig.…”
Section: Discussioncontrasting
confidence: 49%
“…Whey was considered to be representative of the aqueous phase of milk secretion. In this connection White (1960) anddeMan (1962) have shown that the composition of whey is similar to that of milk ultrafiltrate and milk dialysate. The concentration of the different constituents in whey and milk of the first two samples from cows 1, 2, 4, and 5 was similar to previously reported values for cows in mid-lactation (White and Davies 1958).…”
Section: Discussionmentioning
confidence: 92%
“…The results have been expressed in millimoles per litre, thus permitting comparison between different constituents on a concentration basis. This was useful in considering the relationship between sodium, potassium, chloride, and lactose which are mainly in a dissociated form in the milk (White and Davies 1960). It is of less value when considering the anions phosphate and citrate and the cations calcium and magnesium since they form soluble complexes in whey (Jenness and Patton 1959).…”
Section: Discussionmentioning
confidence: 99%
“…Holt et Jenness (1984) utilisant la technique d'ultrafiltration pour la séparation des phases, font état de pourcentages légèrement supérieurs, avec 90% de calcium et 70% de phosphore inorganique sous forme colloïdale. Ces diffé-rences de résultats sont probablement liées à la technique de séparation, comme l'ont montré Davies et White (1960).…”
Section: éQuilibres Salinsunclassified